2020
DOI: 10.1186/s12964-020-0510-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic induction of tumor stemness via the lipopolysaccharide-TET3-HOXB2 signaling axis in esophageal squamous cell carcinoma

Abstract: Background: Esophageal squamous cell cancer (ESCC) is one kind of frequent digestive tumor. The inflammatory environment plays an important role in the tumorigenesis and development of ESCC. Cancer stem cells are a small group of tumor cells with stem cell characteristics, which can potentially hinder the tumor management and treatment. Methods: ELISA was performed to detect the lipopolysaccharide concentration in cancer tissues. qPCR, Western blot, FACS, Immunohistochemistry, Immunofluorescence and Dot blot w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
0
14
0
2
Order By: Relevance
“…TET3 expression was elevated with lipopolysaccharide stimulation via p38/ERK-MAPK pathway in ESCC and negatively correlated with patients' survival. TET3 induced the stemness of ESCC cells (Xu et al, 2020). Our results indicated that TET3 declined in TGF-β1 stimulation and TET3 overexpression inhibited TGF-β1-induced EMT and EMT-mediated metastasis of SKOV3 and 3AO cells by demethylating miR-30d precursor gene, indicating a novel mechanism of epigenetic regulation in ovarian cancer.…”
Section: Introductionmentioning
confidence: 62%
“…TET3 expression was elevated with lipopolysaccharide stimulation via p38/ERK-MAPK pathway in ESCC and negatively correlated with patients' survival. TET3 induced the stemness of ESCC cells (Xu et al, 2020). Our results indicated that TET3 declined in TGF-β1 stimulation and TET3 overexpression inhibited TGF-β1-induced EMT and EMT-mediated metastasis of SKOV3 and 3AO cells by demethylating miR-30d precursor gene, indicating a novel mechanism of epigenetic regulation in ovarian cancer.…”
Section: Introductionmentioning
confidence: 62%
“…2 b), suggesting that LPS was correlated with cell stemness. LPS was reported to upregulate pluripotent marker expression and induce cell stemness [ 29 , 30 ]. qRT-PCR assays revealed that the pluripotent markers Nanog, Sox2, cMyc, Klf4, and Fgf5 were significantly increased, and markers associated with stem cells, such as CD34, CD45, CD90, Tert, and Sox9, were also upregulated in AML12 cells after the administration of LPS (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Higher TET3 is correlated with higher stage and poor clinicopathological features [ 40 ]. Lipopolysaccharide induces the dryness of esophageal squamous cell carcinoma cells by activating the LPS-TET3-HOXB2 signal axis [ 41 ]. In this study, the expression of TET3 in PTC and its relationship with the biological behavior of cancer cells were discussed for the first time.…”
Section: Discussionmentioning
confidence: 99%